Changes in Social, Romantic, and General Life Satisfaction Over the Course of a Substance Use Disorder - Christie, Nina C.; Vojvodic, Vanya; Meda, Pranav; Monterosso, John R. (Frontiers in Psychiatry, 2021)
Background: The pandemic has highlighted the importance of social connection for health and wellbeing. Satisfaction across domains of life is associated with substance use outcomes, such as risk of relapse and mortality. Previous work has delineated the relationship between substance use and social connections, yet there is a lack of research exploring the relationship between substance use and satisfaction with domains of life over time. Methods: We retrospectively assessed satisfaction with social life, romantic life, and general life across five phases of substance use among 339 adults, of whom 289 identify as formerly having a problem with substance use, and a comparison group of 50 who report no history of problematic drug use. We compared those whose primary drug of choice was alcohol, marijuana, methamphetamine, non-prescription opioids, and prescription opioids. Results: Those who used prescription opioids reported a larger drop in satisfaction in social life, romantic life, and general life during the course of substance use than those who used other drugs. However, we report no significant differences in current satisfaction, social wellbeing, or quality of life between people in recovery and people with no history of problematic substance use. Conclusions: These findings ¬– alongside neuropsychological work on the opioid system and sociality – paint a picture that those who used prescription opioids may experience lower satisfaction across life domains during the course of their substance use than those who used other substances. People in recovery, however, show similar levels of satisfaction relative to those who have no history of drug use.